Growth of highly versus moderately trained competitive female artistic gymnasts - Daly, R. M.; Caine, D.; Bass, S. L.; Pieter, W.; Broekhoff, J. (Medicine & Science in Sports & Exercise, 2005)
Purpose: To investigate whether growth was adversely affected in 137 young competitive female artistic gymnasts involved in different training volumes.